Ocular Biometry in Primary Angle-Closure Glaucoma Associated with Retinitis Pigmentosa. (31st December 2017) - Xu, Jiangang; Ouyang, Zhikun; Yang, Yangfan; Cai, Xiaoyu; Wang, Zhonghao; Lin, Mingkai; Zhang, Xiulan; Liu, Xing; Yu, Minbin
Abstract : Background . Retinitis pigmentosa (RP) comprises a group of inherited disorders in which patients typically lose night vision in adolescence and then lose peripheral vision in young adulthood before eventually losing central vision later in life. A retrospective case-control study was performed to evaluate differences in ocular biometric parameters in primary angle-closure glaucoma (PACG) patients with and without concomitant RP to determine whether a relationship exists between PACG and RP. Methods . We used ultrasound biomicroscopy (UBM) to measure anterior chamber depth (ACD). A-scan biometry was carried out to measure lens thickness (LT) and axial length (AL). Propensity score matching and mixed linear regression model analysis were conducted. 23 patients with chronic primary angle-closure glaucoma (CPACG) associated with RP, 21 patients with acute primary angle-closure glaucoma (APACG) associated with RP, 270 patients with CPACG, and 269 patients with APACG were recruited for this study. Results . There were no significant differences on ACDs, ALs, and relative lens position (RLP) (P > 0.05 ) between patients with PACG associated with RP and patients with PACG; however, patients with APACG associated with RP had a significantly greater LT than patients with APACG (P < 0.05 ). Conclusion . Patients with PACG associated with RP had the same biometric parameter characteristic as the patients with CPACG and APACG. This may suggest that RP is a coincidental relationship with angle-closure glaucoma.